1999
DOI: 10.1021/ac981372h
|View full text |Cite
|
Sign up to set email alerts
|

Packed Column Supercritical Fluid Chromatography/Mass Spectrometry for High-Throughput Analysis

Abstract: A supercritical fluid chromatograph was interfaced to a mass spectrometer, and the system was evaluated for applications requiring high sample throughput. Experiments presented demonstrate the high-speed separation capability of supercritical fluid chromatography (SFC) and the effectiveness of supercritical fluid chromatography/mass spectrometry (SFC/MS) for fast, accurate determinations of multicomponent mixtures. A high-throughput liquid chromatography/mass spectrometry (LC/MS) analysis cycle time is reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…The authors concluded that the union of SFC with TOF -MS provided the maximum density of chemical information per unit time. Ventura et al (1999a) demonstrated a threefold reduction in analysis time of SFC/APCI -MS compared with that of LC/APCI -MS for high -throughput multicomponent combinatorial library mixtures. In addition, separation of library components was found to be improved in SFC compared to LC, albeit with modestly reduced sensitivity of SFC/APCI -MS relative to LC/ One of the main problems encountered in the development of preparative SFC instrumentation, as required for high -throughput purifi cation of diverse compounds, is the technology available to collect fractions.…”
Section: Sfc Applications For High -Throughput Analysismentioning
confidence: 99%
“…The authors concluded that the union of SFC with TOF -MS provided the maximum density of chemical information per unit time. Ventura et al (1999a) demonstrated a threefold reduction in analysis time of SFC/APCI -MS compared with that of LC/APCI -MS for high -throughput multicomponent combinatorial library mixtures. In addition, separation of library components was found to be improved in SFC compared to LC, albeit with modestly reduced sensitivity of SFC/APCI -MS relative to LC/ One of the main problems encountered in the development of preparative SFC instrumentation, as required for high -throughput purifi cation of diverse compounds, is the technology available to collect fractions.…”
Section: Sfc Applications For High -Throughput Analysismentioning
confidence: 99%
“…Also, a suitable mobile phase and HPLC column must be selected. As an alternative to HPLC, supercritical fluid chromatography-mass spectrometry (SFC-MS) has been used for the high-throughput analysis of combinatorial libraries [18,19]. The advantages of SFC-MS relative to conventional LC-MS for the purification of combinatorial libraries of compounds are the lower viscosities and higher diffusivities of condensed CO 2 compared to HPLC mobile phases, and the ease of solvent removal and disposal after analysis.…”
Section: Lc-ms Purification Of Combinatorial Librariesmentioning
confidence: 99%
“…Otherwise, molecular ion species might not be formed. Alternatively, supercritical fluid chromatography-mass spectrometry (SFC-MS) has been used for the high-throughput analysis of combinatorial libraries [11,12], and it offers benefits for use during mass spectrometry-based purification of combinatorial libraries. The advantages of SFC-MS relative to conventional LC-MS are (1) lower viscosities and higher diffusivities of condensed CO 2 than HPLC mobile phases, and (2) ease of solvent removal and disposal after analysis.…”
Section: Mass Spectrometry-based Hplc Purification Of Combinatorial Lmentioning
confidence: 99%